Strength behaviour of Corn Husk Ash polymer concrete reinforced with coconut fibre. Issue 1 (1st January 2021) - Appiah-Kubi, Emmanuel; Yalley, Peter Paa Kofi; Sam, Augustine
Abstract: The strength behavior of Corn Husk Ash polymer concrete reinforced with coconut fibre was investigated in this study. The study assessed the suitability of using coconut fibre in concrete to improve its strength properties. The concrete was prepared and cured based on British Standard. Different proportions of the coconut fibre as well as the Corn Husk Ash (CHA) polymer were used in the concrete mixes, with a total of nineteen different mix proportions. The specimens were cured for 28, 90 and 180 days. Compressive strength, tensile splitting strength, torsion and toughness were determined using specimens from the various mixes. Tests were conducted on the 28 th, 90 th and 180 th days of curing, following (Compression) and (Tensile Splitting). Analysis of Variance (ANOVA) test was conducted to determine the differences in the behavior of the different mixes as well as the correlation between the different constructs. The addition of coconut fibre to the concrete improved the toughness, torsion and to some extent the tensile strength of the concrete at the standard curing age of 28 days. CHA as an additive to the concrete resulted in a positive relationship with the Torsion and Toughness properties of concrete at later curing age at 1% level of significance (r = 0.480 and r = 0.730, p < 0.01 respectively). Compressive strength of concrete correlated positively with tensile strength, torsion and toughness of concrete (r = 0.830, r = 0.721 and r = 0.452 respectively with p < 0.01).